Diagnosis and treatment of incomplete internal rectal fistulas - M. O. Chernozhukova; A. M. Kuzminov; S. A. Frolov; Vyacheslav Yu. Korolik; Sh. T. Minbayev; R. R. Eligulashvili (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present literature data on diagnosis and treatment of incomplete internal rectal fistulas. Summary. Incomplete internal rectal fistulas is an insufficiently studied «niche» in proctology. First of all, the definition itself is a terminological void which does not permit definition of these fistulas as a separate nosological entity. Second, as difficult diagnostic procedures are required (due to the absence of external orifice) preoperative assessment of the structure of fistulous tract is complicated. In regards to this the standard treatment of these fistulous does not exist. According to literature data, the frequency of recurrence of incomplete internal fistulous ranges from 8 to 22%. Conclusion. The literature analysis demonstrated that there is a small number of publications in which this problem is considered. Because of lack of classification of this pathology there is no uniform treatment approach which would allow to decrease the risk of relapses, and maintain retention function as well.